2022
DOI: 10.3390/nano12071141
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-Doped Graphene Electrocatalysts for Oxygen Reduction Reaction

Abstract: Developing cheap and earth-abundant electrocatalysts with high activity and stability for oxygen reduction reactions (ORRs) is highly desired for the commercial implementation of fuel cells and metal-air batteries. Tremendous efforts have been made on doped-graphene catalysts. However, the progress of phosphorus-doped graphene (P-graphene) for ORRs has rarely been summarized until now. This review focuses on the recent development of P-graphene-based materials, including the various synthesis methods, ORR perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 118 publications
(152 reference statements)
0
18
0
Order By: Relevance
“…Although the P atom and N atom have the same valence electrons, the P atom shows a larger atomic size and lower electronegativity than the N atom. 57,58 Therefore, its geometric and electronic effects are different from those of the N atom. 59 In the P-doped carbon material, the strong hybridization between the P 3p and C 2p orbitals could convert sp 2 C to sp 3 C, thus forming a pyramid-shaped bonding conguration with three C atoms and a P atom (Fig.…”
Section: P-doped M-n-c Sacsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the P atom and N atom have the same valence electrons, the P atom shows a larger atomic size and lower electronegativity than the N atom. 57,58 Therefore, its geometric and electronic effects are different from those of the N atom. 59 In the P-doped carbon material, the strong hybridization between the P 3p and C 2p orbitals could convert sp 2 C to sp 3 C, thus forming a pyramid-shaped bonding conguration with three C atoms and a P atom (Fig.…”
Section: P-doped M-n-c Sacsmentioning
confidence: 99%
“…60,61 Importantly, the coordination environment could mainly determine the adsorption of oxygen molecules and the binding strength of intermediate species, ultimately leading to enhanced ORR and OER performance. 58,62,63 So far, numerous studies have shown that P-doped nonmetal carbon based ORR catalysts show excellent ORR activity. 64,65 Yang et al 60 synthesized a kind of N and P co-doped non-metal carbon catalyst, and its active structure was Fig.…”
Section: P-doped M-n-c Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doped P mostly exists in P-C (Figure 4E). Because the electronegativity of P (2.19) is lower than C (2.55), P atom with positive charge will be induced and new ORR active sites may be generated in alkaline medium [2]. Moreover, the presence of phosphorus atoms in P-O is beneficial for enhancing the electronegativity of the O atom, thereby promoting the charge delocalization of nearby C atoms, increasing the adsorption on O 2 [37][38][39].…”
Section: Characterization Of Npfe-cmentioning
confidence: 99%
“…Oxygen reduction reaction (ORR) kinetics pose a major challenge to the development of energy conversion devices, especially metal-air batteries and fuel cells [1][2][3][4]. Platinum based noble metal catalysts are recognized as the best catalysts for ORR.…”
Section: Introductionmentioning
confidence: 99%